2021
DOI: 10.22270/ujpr.v6i4.643
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Urinary Tract Infection: Clinical Signs, Bacterial Causes and Antibiotic Susceptibility

Abstract: Background and objective: Urinary tract infections (UTIs) are the neglected infection in children from the side of study its clinical symptoms, causative organisms and their antibiotic sensitivity. This investigation searches for determine clinical symptoms frequency, prevalence rate, bacterial features, and  antibiotic sensitivity of bacterial urinary tract infection in children attending private children’s health center in Sana’a city. Methods: In a prospective study carried out over a 24-month period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirms the alarming rate of resistance of Grampositive bacteria to the polyclonal antimicrobials penicillin (100%), erythromycin (85.8%) and amoxicillin (78.6%) which was similar compared to previous studies conducted in Yemen before 29-42 . This may be because the experimental treatment of isolates and/or the random and repeated use of these antibiotics by unskilled practitioners along with the lack of guidelines for antibiotic use participate a fundamental role in the emergence and spread of resistance 13,28, 41 . Limitations This study did not address anaerobic bacteria pathogens due to limited laboratory facilities.…”
Section: Discussionmentioning
confidence: 99%